FEATURES OF THE DEVELOPMENT OF JADIDISM IN TURKESTAN - Shodiev R; Shodieva S (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the features of the development of the movement jadidism, which emerged as an educational movement at the turn of the XIX-XX centuries and went deep into history until the end of the 20s of the XX century. This movement still arouses great interest not only in Turkestan, but also far beyond its borders. The use of socio-political, moral, and philosophical ideas and teachings of the Turkestan jadids is important in the formation of philosophical thinking and strengthening the ideological immunity of young people. The ideology of jadidism was widely influenced in Central Asia by the energetic work of the Islamic modernist Mahmud Khoja Behbudi.